Some Achievements and Challenges of Dental Anthropology - Luna, Leandro Hernan (2016)
Dental Anthropology has produced a huge amount of information in the last decades, covering many different aspects of human biological and cultural life. For the last twenty years, a process of diversification and specialization occurred, that sometimes precluded the development of macroscale comparative studies, except for a few exceptional cases. Some reflections and critical debate have to be done to overcome these limits and to arrive to more consensual methodological procedures. The generation, analysis and conservation of new and previously known documented human osteological collections, and the use of compatible methodologies continue to be fundamental to obtain proxy data and generate adequate protocols to carry out comparative studies involving research projects from different parts of the world.